Metro Insan Mulia Foundation's Social Capital and Its Determinants of Civic Engagement in Mataram City: Modal Sosial Metro Insan Mulia Foundation Dan Determinannya Terhadap Civic Engagement di Kota Mataram - Mahendra, Wisnu; Nasiwan , Nasiwan (Institut Riset dan Publikasi Indonesia, 2026)
Mataram City faces declining community participation, weakening mutual cooperation, and low literacy in zakat and waqf within the partner organization, Metro Insan Mulia Foundation. This activity aims to identify, analyze, and strengthen social capital in promoting civic engagement. The method used is a participatory qualitative approach through interviews, observations, and documentation involving three key informants: the chairman, program manager, and HRD. The activity was conducted through preparation, implementation, and evaluation stages, with data analyzed using Nvivo 12 Pro. The evaluation results indicate that strengthening social capital through bonding, bridging, linking, and the internalization of organizational values and norms enhances partner understanding, expands networks, and builds public trust. The impact on the partner includes increased volunteer involvement, higher community participation in social programs, and improved organizational capacity. Additionally, this activity produced a systematic mapping of supporting and inhibiting factors of civic engagement as a basis for sustainable program development. In conclusion, strengthening value-based and professional social capital is effective in fostering inclusive and sustainable civic engagement.